Technology enhanced learning and augmented reality : an application on multimedia interactive books - Dias, Albertina (2009)
Multimedia Interactive Book (miBook) reflects the development of a new concept of virtual interpretation of traditional text books and audio-visual content. By encompassing new technological approaches, using augmented reality technology, allows the final user to experience a variety of sensorial stimuli while enjoying and interacting with the content; therefore enhancing the learning process. miBook stands for a global educational intention to enable people not only to access but also to appropriate intellectually valuable contents coming from different linguistic and cultural contexts.